Validating the Italian Version of the Disgust and Propensity Scale-Revised - Martoni, Riccardo M.; Rancoita, Paola M. V.; Di Serio, Clelia; Brombin, Chiara (Frontiers in Psychology, 2017)
The aim of this work is to evaluate the factor structure and psychometric properties of the Italian version of the Disgust Propensity and Sensitivity Scale-Revised (DPSS-R, 16 items) in two samples taken from the general population. In the first study, 285 participants completed the DPSS-R questionnaire through a web-based survey. Exploratory factor analysis for ordinal Likert-type data supported the existence of four underlying factors, reflecting self-focused disgust, disgust propensity, somatic anxiety and disgust sensitivity. In the second study, an independent sample of 293 participants was enrolled as a test set to validate the factor structure obtained in the exploratory phase. The factor solution was confirmed, but showed quite highly correlated latent factors. We fitted the model and tested whether or not the bifactor structure was better than the previous one (four correlated factors). Actually, we had evidence supporting the presence of a general factor, providing a measure of disgust susceptibility, along with the four specific factors previously defined. This result could be useful also from the clinical perspective since the DPSS-R questionnaire will be used in clinical context, where underlying factors may be related to different and specific psychopathological profiles. Finally, we examined and visualized the interrelationships among the four DPSS-R factors and the external scales (Anxiety Sensitivity, Disgust Scale and Padua) using a graphical model approach.